You are on page 1of 66

# Mathematical Methods for Physicists

by G. Arfken
Chapter 13: Special Functions
Reporters:黃才哲、許育豪
Hermite Functions
• Generating functions - Hermite polynomial
• Recurrence relation
• Special values of Hermite polynomial
• Alternate representations
• Orthogonality
• Normalization
• Application
Generating Functions

tn
g ( x, t ) = e −t +2tx = ∑ H n (x )
2
• Define (1)
n =0 n!
• Take y = −t 2 + 2tx
∞ n
y
– expand ey = ∑ n!
n =0

– We have H 0 (x ) = 1
H1 ( x ) = 2 x
H 2 (x ) = 4 x 2 − 2
H 3 ( x ) = 8 x 2 − 12 x
H 4 ( x ) = 16 x 4 − 48 x 2 + 12
H 5 ( x ) = 32 x5 − 160 x 3 + 120 x
H 6 ( x ) = 64 x 6 − 480 x 4 + 720 x 2 − 120
Recurrence Relations (1/4)
• H n+1 ( x ) = 2 xH n ( x ) + 2nH n−1 ( x ) (2)
d ⎛ −t 2 + 2tx ∞ H n ( x ) n ⎞
⎜e =∑ t ⎟
dt ⎝ n =0 n! ⎠

H n ( x ) n−1
⇒ (− 2tx + 2 x )e −t 2 + 2 tx
=∑ t
n =0 (n − 1)!

H n ( x ) n ∞ H n ( x ) n−1
⇒ (− 2tx + 2 x )∑ t =∑ t
n =0 n! n =0 (n − 1)!

H n ( x ) n+1 ∞
H n ( x ) n ∞ H n ( x ) n−1
⇒ −2∑ t + 2 x∑ t =∑ t
n =0 n! n =0 n! n =1 (n − 1)!
Recurrence Relations (2/4)
0
• The coefficient of t
– 2 xH 0 ( x ) = H1 ( x )
• The coefficient of t n (n ≠ 0)

( ) ( ) ( )
– 2 H n −1 x + 2 x H n x = 2 x H n + 1 x
(n − 1)! n! n!
⇒ 2 nH n −1 ( x ) + 2 xH n ( x ) = H n +1 ( x )
Recurrence Relations (3/4)
• H n′ ( x ) = 2nH n −1 ( x ) (3)
– Differentiate the generating function with respect
to x d ⎛ ∞
H (x ) ⎞
⎜e −t 2 + 2 tx
=∑ n
tn ⎟
dx ⎝ n =0 n! ⎠

H n′ ( x ) n
⇒ 2te −t + 2 tx
=∑
2
t
n =0 n!

H n ( x ) n ∞ H n′ ( x ) n
⇒ 2t ∑ t =∑ t
n =0 n! n =0 n!

H n ( x ) n +1 ∞ H n′ ( x ) n
⇒ 2∑ t =∑ t
n =0 n! n =0 n!
Recurrence Relations (4/4)
n
• The coefficient of t

n=0 H 0′ ( x )
– = H 0′ ( x ) = 0
0!
– n>0 H n −1 ( x ) H n′ ( x )
2 =
(n − 1)! n!
⇒ H n′ ( x ) = 2 nH n −1 ( x )
Value at x = 0

z g ( x, t ) = e − t 2 + 2tx

⇒ e −t
2
= 1+
(− t ) (− t )
+
2 2 2
t2 t4 ∞
+ " = 1 − + − " = ∑ (− 1)
k t 2k

1! 2! 1! 2! k =0 k!
∞ 2k ∞ n
⇒ ∑ (− 1) =∑ H n ( x )
k t t
k =0 k! n=0 n!
k (2k )!
n = 2k : H 2k (0) = (− 1)
k!
n = 2k + 1 : H 2k +1 (0) = 0
Parity Relation
H n ( x ) = (− 1) H n (− x )
k

– Expand the generating function
– We have H0 (− x) =1
H1(− x) = −2x = (−1) H1(x)
1

H2 − x = 4 − x − 2 = −1 H2 (x)
( ) ( ) ( )
2 2

2 3

4 2 4

5 3 5

## H6 (x) = 64(− x) − 480(− x) + 720(− x) −120= (−1) H6 (x)

6 4 2 6

"
Rodrigues Representation of Hn(x)

tn
g (x , t ) = e − t + 2 tx
= e −t ∑
+ 2 tx − x + x
= e x e − (t − x ) = H n (x )
2 2 2 2 2 2

z n!
n=0
z Differentiation of the generating function n times
with respect to t (note that d e −(t − x ) = − d e −(t − x ) ) 2 2

dt dx

z Set t=0
⇒ H n ( x ) = (− 1) e x
n 2 d n − x2
dx n
e ( )
Calculus of Residues
−m −1
• Multiply the generating function by t
• Integrate around the origin
• We have Hm (x) =
m! −m−1 −t 2 +2tx
2πi ∫ t e dt
Series Form
2 ⋅ n! 4 ⋅ n!
H n ( x ) = (2 x ) − (2 x ) + (2 x )n−2 ⋅1⋅ 3 + "
n n−2

(n − 2)!2! (n − 4)!4!
[n 2 ]
⎛n⎞
= ∑ (− 2 ) (2 x ) ⎜⎜ ⎟⎟1 ⋅ 3 ⋅ 5 ⋅" ⋅ (2 s − 1)
s n−2 s

s =0 ⎝ 2s ⎠
[n 2 ]
= ∑ (− 2 ) (2 x )
s n−2 s n!
s =0 (n − 2s )! s!
Orthogonality
• By recurrence relations,
H n'' ( x ) − 2 xH n' ( x ) + 2nH n ( x ) = 0
ψ ( ) = −x 2
H n (x )
2

• Let n x e
– We have ψ n'' ( x ) + (2n + 1 − x 2 )ψ n ( x ) = 0 (4)
– which is self-adjoint and orthogonal in x ∈ (− ∞ , ∞ )
Normalization
− x2
• Multiply (1) by itself and by e
m n∞
= ∑ e Hm(x)Hn (x)
−x −s +2sx −t +2tx
2 2
−x
2 s t 2
e e e
m,n=0 m!n!
• Integrate x from − ∞ to ∞ , and consider the
orthogonal property

(st )n ∞ ∞ ∞

∑ n!n! ∫ e [H (x )] dx = ∫ e−x − x − s + 2 sx −t + 2 tx
dx = ∫e
− ( x − s −t )2 2 st
2 2 2 2 2

n e dx
n =0 −∞ −∞ −∞

2 n (st )
1 1 ∞ n
=π e 2 2 st
=π ∑ 2

n =0 n!
• Equating coefficients of like powers of st to obtain

[H n (x )] dx = 2 π
1
∫e
− x2 2 n 2
n!
−∞
Simple Harmonic Oscillator
= 2
∇ ψ ( x ) + Kz 2 = Eψ ( z )
1
• − 2m 2
(5)
d 2ψ ( x )
• Reduce to the form of
dx 2
( )
+ λ − x 2 ψ (x ) = 0
• Which is (4) with λ = 2n + 1
• Hence
ψ n (x ) = 2 −n 2
π −1 4
(n!)
−1 2 − x 2 2
e H n (x )
Laguerre Functions
• Laguerre polynomial
• Associated Laguerre polynomials
• Application
Laguerre Polynomial
• Laguerre’s differential equation
• Generating functions - Laguerre polynomial
• Alternate representations - Rodrigues’ formula
• Recurrence relation
• Orthogonality
Laguerre’s Differential Equation (1/2)
• xy" ( x) + (1 − x) y '+ ny ( x) = 0 (6)
• Denote solution as yn , since y will depend on n .
• By contour integral,
− xz /(1− z )

v∫
yn ( x) =
1 e dz
(7)
2π i (1 − z ) z n +1

## • The contour encloses the origin but does not enclose

the point z = 1 , since

v∫ v∫
− xz /(1− z ) − xz /(1− z )

yn′ ( x) = −
1 e dz yn′′( x) = −
1 e dz
2π i (1 − z) z 2 n
, 2π i (1 − z) z 3 n−1
Laguerre’s Differential Equation (2/2)
• Substituting into the left-hand side of (6), we obtain
1 ⎡ x 1− x n ⎤ − xz (1− z )

v ⎢
2π i ⎢⎣ (1 − z ) z
3 n −1
− + n +1 ⎥
(1 − z ) z (1 − z ) z ⎥⎦
2 n
e dz

− xz /(1− z )
1 d ⎡ e ⎤
– Which is equal to

v ⎢
2π i dz ⎣ (1 − z ) z ⎦
n ⎥ dz

## • If integrate around a contour so that the final point

equals to the initial point, the integral will vanish,
thus verifying that (7) is a solution to the Laguerre’s
equation
Generating Functions
• Define the Lagurre polynomial ,Lby( x )
n
− xz /(1− z )
1 e n+1 dz
2π i v∫ (1 − z ) z
Ln ( x) =
– This is exactly what we would obtain from the series
, (8)
e − xz (1− z ) ∞
=
g ( x, z ) by
• If multiply = ∑ Ln (around
and integrate < 1 only the
x) z n the zorigin,
term in the series 1 −remains.
z n =0
• Identify −n −1generating function for the Lagurre
aszthe
polynomials.− 1
z
g ( x, z )
Rodrigues’ Formula
• With the transformation
n −s

x
L (x ) =
s x e s e

xz
= s−x z = ds
1− z ,
s , n 2πi (s − x )n +1

## • Which is the new contour enclosing s = x in the

s-plane
• By Chauchy’s integral theorem (for derivatives)
ex d n n −x
Ln ( x ) = (x e ) (integral n ) (9)
η! dx n
Series Form
• From these representations of Ln (x ) , we find the series
form for integral n
( −1) ⎡ n n −1 n ( n − 1) n − 2 ⎤
n 2 2 2

L ( x) = ⎢x − x + x − " + ( −1) n !⎥
n n
n
n ! ⎢⎣ 1! 2! ⎥⎦
n m n n−s
n ! x n ! x
= ∑ (−1) m = ∑ (−1) n − s
m=0 (n − m)!(m)!m ! s =0 (n − s )!(n − s )! s ! (10)
• We have L0 ( x ) = 1
L1 ( x ) = − x + 1
2 ! L2 ( x ) = x 2 − 4 x + 2
3! L3 ( x ) = − x 3 + 9 x 2 − 18 x + 6
4 ! L 4 ( x ) = x 4 − 16 x 3 + 72 x 2 − 96 x + 24 "
Recurrence Relations
• Differentiate the generating function, with respect to z
and x ,
- ( n + 1) Ln +1 ( x ) = ( 2n + 1 − x ) Ln ( x ) − nLn−1 ( x )
= 2 Ln ( x ) L n−1 ( x ) − [(1 + x ) Ln ( x ) − L n−1 ( x )] /( n + 1)
- xL'n ( x ) = nL n ( x ) − nL n −1 ( x )

## • For reasons of numerical stability, these are used for

machine computation of numerical values of Ln (x ) .
• The computing machine starts with known numerical
values of L1 (x ) and L0 (x ) .
Orthogonality
• The Laguerre differential equation is not self-adjoint and
the Laguerre polynomials do not by themselves form an
orthogonal set
• The related set of function n ϕ ( x ) = e −x/2
Ln ( x) is
orthonormal for interval 0 ≤ x ≤ ∞ ,

that is ∫0 e − x Lm ( x) Ln ( x)dx = δ m ,n
which can be verified by using the generating function
• The orthonormal function ϕn (x ) satisfies the differential
equation
xϕ ′′( x) + ϕ ′( x) + (n + 1 / 2 − x / 4)ϕ ( x) = 0
– which has the Sturm-Liouville form (self-adjoint).
Associated Laguerre Polynomials
• Associated generating functions - Laguerre
polynomial
• Associated recurrence relation
• Associated Laguerre’s differential equation
• Alternate representations - associated Rodrigues’
formula
• Associated orthogonality
Associated Laguerre Polynomials
k
d
• Associated Laguerre polynomials n Lk
( x ) = ( − 1) k
k
[ Ln + k ( x)]
dx
– From the series form of Ln (x )
x 2
(k + 2)(k + 1)
– L0 ( x ) = 1, L1 ( x) = − x + k + 1, L ( x) = − (k + 2) x + "
k k k
2
2 2
n
(n + k )!
– In general, L ( x) = ∑ (−1)
k m
, (k > −1)
(n − m)!(k + m)!m !
n
m=0
• A generating function may be developed by
differentiating the Laguerre generating function k
times
e − xz /(1− z ) ∞

L L ( x ) z
(n + k )!
n =0

## and Lkn (0) =

n!k!
Recurrence Relations
• Recurrence relations can easily be derived from the
generating function or by differentiating the Laguerre
polynomial recurrence relations.
– (n + 1) Lkn+1 ( x) = (2n + k + 1 − x) Lkn ( x) − (n + k ) Lkn−1 ( x)
– xLkn'' ( x) = nLkn ( x) − (n − k ) Lkn −1 ( x)
Associated Laguerre Equation
• Differentiating the Laguerre’s differential equation k
times, we have the associated Laguerre equation
– xLkn' ( x) = (k + 1 − x) Lkn' ( x) + nLkn ( x) = 0 (11)
Associated Rodrigues Representation
• A Rodrigues representation of the associated
Laguerre polynomial is
x −k n
– Lk ( x) = e x d − x n+k
n n
( e x )
n! dx
• Note that all of these formula Lkn (x ) reduce to the
corresponding expressions for Ln (x ) when k = 0 .
• The associated Laguerre equation is not self-adjoint,
but it can be put in self-adjoint form by multiplying
−x k
e x
∞ (n + k )!
∫ δ m,n
−x
– We obtain e x L ( x) L ( x)dx =
k k
n
k
m
0 n!
ψ
– Let n
k
( x ) = e −x 2 k 2 k
x Ln ( x ) , n ( x ) satisfies the
ψ k

xψ nk '' ( x ) + ψ nk ' ( x ) + [− x 4 + (2n + k + 1) 2 − k 2 4 x ]ψ nk ( x ) = 0
• Define n φ k
( x ) = e − x / 2 ( k +1) / 2 k
x Ln ( x)
• Substitution into the associated Laguerre equation
yields φnk '' ( x ) + [− x 4 + (2n + k + 1) 2 − k 2 4 x ]φnk ( x ) = 0(12)
– The corresponding normalization integral is
∞ (n + k )!

−x k +1 k
e x L ( x) L ( x)dx =
n
k
n (2n + k + 1)
{ }
0 n!
– It shows that φn ( x ) do not form an orthogonal set
k

## (except with x −1 as the weighting function) because

of the term (2 n + k + 1) 2 x
Hydrogen Atom (1/4)
• The solution
2
of2 the Schödinger wave equation
h Ze
– − ∇ψ −
2
ψ = Eψ
• The angular dependence of ψ is YLM (θ ,ϕ )
2m r

## • The radial part R (r ) , satisfies the equation

h 2 1 d ⎛ 2 dR ⎞ Ze 2 h 2 L( L + 1)
–− ⎜r ⎟− R+ R = ER (13)
2m r dr ⎝ dr ⎠ r
2
2m r 2
Hydrogen Atom (2/4)
• By use of2abbreviations ρ = α r 8mE
, α = − 2 (E < 0) ,and
2

2mZe h
λ=
αh 2
• (13) becomes
1 d ⎡ 2 dχ ( ρ ) ⎤ ⎡ λ 1 L( L + 1) ⎤
ρ 2 dρ ⎢ ρ dρ ⎥ + ⎢ ρ − 4 − ρ 2 ⎥ χ ( ρ ) = 0
⎣ ⎦ ⎣ ⎦ (14)
• where χ (ρ ) = R(ρ α )
Hydrogen Atom (3/4)
• A comparison with (12) for n (x ) shows that (14) is
φ k

satisfied by ρχ ( ρ ) = e − ρ / 2 ρ L +1 L2λL−+L1−1 ( ρ )
– In which k is replaced by 2L +1 and λ − L − 1
• Since the Laguerre function of nonintegral n would
diverge as ρ ne ρ, λ must be an integer n =1,2,3,"
• The restriction on λ has the effect on quantizing the
2 4
energy E = − Z me
n
2n 2 h 2
Hydrogen Atom (4/4)
2
2Z me Z 2Z
• By the result of En , we have ρ = r, α = 2 2
=
na0 h n na0
h2
• With a0 = 2 the Bohr radius
me
• We have the normalized hydrogen wave function
3 1/ 2
⎡ ⎛ 2Z ⎞ (n − L −1)! ⎤ −αr / 2
ψ nLM (r,θ ,ϕ) = ⎢ ⎜ ⎟ ⎥ e (α r ) L 2 L+1
Ln−L−1 (α r )YL (θ ,ϕ )
M

## ⎣ ⎝ na0 ⎠ 2n(n + L)! ⎦

Chebyshev Polynomials
• Chebyshev polynomials
• Generating function
• Recurrence relations
• Special values
• Parity relation
• Rodrigue’s representations
• Recurrence relations – derivatives
• Power series representation
• Orthogonality
• Numerical applications
Generating Function
• The generating function for the ultraspherical or
Gegenbauer polynomials
2β π 1/ 2 ∞

2 β +1/ 2
(1 − 2 xt + t )
= ∑
( β − 1/ 2)! n =0
Tn
β
( x )t n
, t <1
(15)

## – β = 0 gives rise to the Legendre polynomials

– β = ±1 2 , generate two sets of polynomials known
as the Chebyshev polynomials
Chebyshev Polynomials of Type I (1/2)
• With β = −1 2 ,the t and x dependence on the left of
(15) disappears and the ( β − 1 2 ) ! blows up
• To avoid the problem,
– differentiate (15) with respect to t and let β = −1 2
x−t π ∞
to yield =
1 − 2 xt + t
2 ∑ nnT −1 / 2

2 n =0
( x )t n −1

## • Then multiply 2t and add one to obtain

1− t2 π ∞

1 − 2 xt + t 2
= 1+
2
∑ 2 nT
n=0
n
−1 / 2
( x )t n
Chebyshev Polynomials of Type I (2/2)
π
• For n > 0, define Tn ( x) = nTn−1/ 2 ( x)
2
1− t 2 ∞

• Then 1 − 2 xt + t 2 = 1 + 2 ∑
n =0
Tn ( x )t n
(16)

## • For n = 0, define T0 ( x) = 1 to preserve the

recurrence relation
Chebyshev Polynomials of Type II

21/ 2
• With β = +1 2 , (15) becomes (1 − 2 xt + t 2 )
= π 1/ 2

n =0
Tn
1/ 2
( x )t n

π 1/ 2
– Define Tn ( x) = U n ( x)
2
– This gives us ∞
1
= ∑U n ( x)t n
1 − 2 xt + t 2 n =0 (17)
– The functions U n (x ) generated by (1 − 2tx + t ) 2 −1

## are called the Chebyshev polynomials of type II

Recurrence Relations
• From generating functions (16) and (17), we obtain
Tn +1 ( x) − 2 xTn ( x) + Tn −1 ( x) = 0 (18)
U n +1 ( x) − 2 xU n ( x) + U n −1 ( x) = 0 (19)
• Then, use the generating functions for the first few
values of n and these recurrence relations to obtain
the high-order polynomials
Special Values
Tn (1) = 1
Tn (−1) = (−1) n
T2 n (0) = (−1) n
T2 n+1 (0) = 0
U n (1) = 1
U n (−1) = (−1) n
U 2 n (0) = (−1) n
U 2 n+1 (0) = 0
Parity and Rodrigue’s Representations
• Parity relation
– Tn ( x) = (−1) n Tn (− x) and Un (x) = (−1)nUn (−x)
• Rodrigue’s representations

(−1) n π 1/ 2 (1 − x 2 )1/ 2 d n 2 n −1 / 2
T
– n ( x ) = [(1 − x ) ]
2 (n − 1 / 2)!
n
dx n

(−1) n π 1/ 2 (n + 1)1/ 2 dn 2 n +1 / 2
– U n ( x) = n+1 [(1 − x ) ]
2 (n + 1 / 2)!(1 − x ) dx2 1/ 2 n
Recurrence Relations – Derivatives
• From the generating functions, obtain a variety of
recurrence relations involving derivatives
– (1 − x 2 )Tn' ( x) = − nxTn ( x) + nTn −1 ( x)
– (1 − x 2 )U ' ( x) = −nxU ( x) + (n + 1)U ( x)
n n n −1
• From (18) and (19)
Type I satisfies (20)
(1 − x )Tn ( x) − xTn ( x) + n Tn ( x) = 0
2 '' ' 2
Type II satisfies (21)
− x )Un (x) − 3xU (x) + n(n + 2)Un (x) = 0
2 '' '
• The Gegenbauer’s(1equation n

(1 − x 2
) y ''
− 2(1 + β ) xy '+ nof(nthese
– which is a generalization + 2 β equations
+ 1) y = 0
Power Series Representation
• Define n +1
V ( x ) = 1 − x 2
U n ( x)
• From the generating function, or the differential
equations
– T n ( x ) = ∑ ( − 1) m ( n − m − 1)! ( 2 x ) n − 2 m
n [n / 2]
2 m m ! ( n − 2 m )!
[n / 2]
( n − m )!
– U n (x) = ∑ ( − 1)
m
m

m ! ( n − 2 m )!
(2 x)n−2m

V
• n (x) = 1− x2
(⎣ 1 ) ( 3 )
⎡ n
xn−1
− n
xn−3
(1− x2
) + (5)
n
xn−5
(1− x ) −"⎤⎦
2 2

• Finally, we obtain
Tn ( x) + iVn ( x) = [ x + i (1 − x ) ] , x ≤ 1
2 1/ 2 n
Orthogonality
• If (20) and (21) are put into self-adjoint form, we
obtain w(x ) = (1 − x ) and w ( x ) = (1 − x ) as their
2 −1 2 2 12

weighting factors
• The resulting orthogonality integrals are
⎧ 0, m ≠ n
1 ⎪
∫−1 m n ⎨π 2, m = n ≠ 0
2 −1/ 2
T ( x )T ( x )(1 − x ) dx =
⎪π , m=n=0

⎧ 0, m ≠ n
1 ⎪
∫−1Vm ( x)Vn ( x)(1 − x ) dx = ⎨π 2, m = n ≠ 0
2 −1/ 2

⎪ 0, m=n=0

1 π
∫ −1
U m ( x )U n ( x ) (1 − x 2 ) 1 / 2 d x =
2
δ m ,n
Numerical Applications
• The Chebyshev polynomials are useful in numerical
work over an interval [− 1,1 ] because
– Tn ( x ) ≤ 1, − 1 ≤ x ≤ 1
– The maxima and minima are of comparable
magnitude
– The maxima and minima are spread reasonably
uniformly over the range [− 1,1 ]
– These properties follow from Tn ( x ) = cos(n cos −1 x )
Hypergeometric Functions
• Hypergeometric equations
• Contiguous function relations
• Hypergeometric representations
Hypergeometric Equations
• Hypergeometric equations
– x(1 − x) y′′( x) + [c − (a + b + 1) x] y′( x) − aby ( x) = 0
– A canonical form of a linear second-order differential
equation with regular singularities at
x = 0, 1, ∞ .
• One solution is
a ⋅ b x a(a +1)b(b +1) x2
y( x) = 2 F1 (a, b, c; x) = 1+ +
c 1! c(c +1) n!
– Which is known as the hypergeometric equation or
hypergeometric series
x <1
– The range of convergence: x = 1 for ,
and , for
c > a + b −1 x = −1 c > a+b
Pochhammer Symbol
• In terms of the Pochhammer symbol,
(a + n − 1)!
– n
( a ) = a ( a + 1)( a + 2 ) " ( a + n − 1) = and (a) 0 = 1
(a − 1)!
– The hypergeometric equations becomes
∞ n
( a ) n (b ) n x
2 F1 ( a , b , c ; x ) = ∑
n=0 (c )n n!
– The leading subscripts 2 indicates that two
Pochhammer symbols appear in the numerator
and the final subscript 1 indicates one
Pochhammer symbol in the denominator
Representation of Elementary Functions
• Many elementary functions can be represented by the
hypergeometric equations
• For example
– ln(1 + x) = x2 F1 (1,1,2;− x)
– complete elliptic integrals
π /2 π
K =∫ (1 − k sin θ ) dθ =
2 2 1/ 2
F
2 1 (1 / 2, −1 / 2,1; k 2
)
0 2
π /2 π
E=∫ (1 − k sin θ ) dθ =
2 2 1/ 2
F
2 1 (1 / 2, −1 / 2,1; k 2
)
0 2
Hypergeometric Equations
• Another solution
1− c
– y ( x ) = x 2 F1 ( a + 1 − c, b + 1 − c, 2 − c; x ), c ≠ 2,3, 4,"
– It shows that if c is an integer, either the two
solutions coincide or one of the solutions will
blow up.
– In such case the second solution is expected to
include a logarithmic term
Alternate Forms
• Alternate forms of hypergeometric equation include
d2 ⎛1− z ⎞ d ⎛1− z ⎞ ⎛1− z ⎞
(1 − z ) 2
2
y⎜ ⎟ − [( a + b + 1) z − ( a + b + 1 − 2 c )] y⎜ ⎟ − aby ⎜ ⎟=0
dz ⎝ 2 ⎠ dz ⎝ 2 ⎠ ⎝ 2 ⎠
d2 ⎡ 1 − 2c ⎤ d
(1 − z ) 2 y ( z ) − ⎢(2a + 2b + 1) z +
2 2
⎥ y ( z 2
) − 4 aby ( z 2
)=0
dz ⎣ z ⎦ dz
Contiguous Function Relations
• We expect recurrence relations involving unit
changes in the parameters a , b , and c .
• Usual nomenclature for the hypergeometric
functions in which one parameter changes by + 1 or − 1
is “contiguous function”
• For example,
(a − b){c(a + b − 1) + 1 − a 2 − b 2 + [(a − b) 2 − 1](1 − x))} 2 F1 (a, b, c; x)
= (c − a)(a − b + 1)b 2 F1 (a − 1, b + 1, c; x) + c − a)(a − b + 1)a 2 F1 (a + 1, b − 1, c; x)
Hypergeometric Representations (1/2)
• Gegenbauer function,
β (n + 2 β )! 1− x
– Tn ( x) = β 2 F1 ( − n, n + 2 β + 1,1 + β ; )
2 n! β ! 2
• Legendre and associate Legendre functions
1− x
P
– n ( x ) = F
2 1 ( − n, n + 1,1; )
2
2 m−2
( n + m )! (1 − x ) 1− x
– Pn ( x) =
m
2 F1 ( m − n, m + n + 1, m + 1; )
(n − m)! 2 m! m
2
– Alternate forms are
(2n+1)! (2n)!
P2n+1(x) = (−1) 2n
n
x2 F1(−n, n+3/2,3/2; x2) P2n (x) = (−1)n 2n F
2 1 (− n, n +1/2,1/2; x2
)
2 n!n! 2 n!n!
(2n+1)! (2n −1)!
= (−1)n x2 F1(−n, n+3/2,3/2; x2) = (−1)n F
2 1 (− n , n +1/2,1/2; x2
)
(2n)!! (2n)!!
Hypergeometric Representations (2/2)
• In terms of hypergeometric functions, the
Chebyshev functions become
– T n ( x ) = 2 F1 ( − n , n ,1 / 2 ; 1 − x )
2 1− x
– U n ( x) = (n + 1) 2 F1 (−n, n + 2,3 / 2; )
21− x
– Vn ( x) = 1 − x n 2 F1 (−n + 1, n + 1,3 / 2;
2
)
2
• The leading factors are determined by direct
comparison of complete power series, comparison
of coefficients of particular powers of the variable,
or evaluation at x = 0 or x = 1, etc
Confluent Hypergeometric Functions
• Confluent hypergeometric equation
• Confluent hypergeometric representations
• Integral representation
• Bessel and modified Bessel functions
• Hermite functions
• Miscellaneous cases
Confluent Hypergeometric Equation
• xy′′( x) + (c − x) y′( x) − ay ( x) = 0
• May be obtained from the hypergeometric equation
by merging two of its singularities
• The resulting equation has a regular singularity at
x = 0 and an irregular one at x = ∞ .
Solutions
• One solution of the confluent hypergeometric
equation is y ( x) = 1 F1 (a, c; x) = M (a, c; x) = 1 + a x a ( a + 1) x 2
+ +"
– Which is convergent for all finite x c 1! c(c + 1) n !
– In terms of the Pochhammer symbols, we have

(a)n xn which becomes a polynomial if
M (a, c; x) = ∑
the parameter n=0 (c)n n! is or a negative integer
• A second solution is
a 1
y ( x) = x1−c M (a, a + 1;− x), c ≠ 2,3,4, "
• The standard form of the Confluent hypergeometric
equation is a linear combination of both solutions

π ⎡ M (a, c; x) x M (a + 1 − c, 2 − c; x) ⎤
1− c
U (a, c; x) = ⎢ − ⎥
sin π c ⎣ (a − c)!(c − 1)! (a − 1)!(1 − c)! ⎦
Representations
• Numerous elementary functions may be represented
by the confluent hypergeometric function
• For example
2 x −t 2
– Error function erf ( x) = 1/ 2 ∫0 e dt = 1/ 2 xM (1 / 2,3 / 2; x 2 )
2

π π
– Incomplete gamma function
γ (a, x ) = ∫ e −t t a −1dt = a −1 x a M (a, a + 1;− x ) , Re{a} > 0
x

0
Integral Representation (1/2)
• Confluent hypergeometric functions in integral forms
Γ ( c ) 1

– M (a, c; x) = xt a −1 c − a −1
e t (1 − t ) dt ,
Γ ( a )Γ ( a − c ) 0
Re{c} > Re{a} > 0

1 ∞ − xt a −1
– U ( a , c; x ) = ∫ e t (1 − t ) c − a −1
dt , Re{x} > Re{a} > 0
Γ(a ) 0
Integral Representation (2/2)
• Three important techniques for deriving or verfying
integral representations:
– Transformation of generating functions and
Rodrigues representations
– Direct integration to yield a series
– Verification that the integral representation
satisfies the differential equation, exclusion of
other solution, verification of normalization
• The confluent hypergeometric equation is not self-
• Define M kµ ( x) = e − x / 2 x µ +1/ 2 M ( µ − k + 1 / 2,2µ + 1; x)
– This new function is a Whittaker function which
⎛ 1 k 1/ 4 − µ 2 ⎞
M ( x) + ⎜⎜ − + +
n
kµ 2
⎟⎟ M kµ ( x) = 0
⎝ 4 x x ⎠
– The corresponding second solution is
Wkµ ( x) = e − x / 2 x µ +1/ 2U ( µ − k + 1 / 2,2µ + 1; x)
Bessel and Modified Bessel Functions
• Kummer’s first formula M (a, c; x) = e x M (c − a, c;− x) is
useful in representing Bessel and modified Bessel
functions
• Representation in the form of the confluent
hypergeometric equation −ix v
e ⎛ x ⎞
– Bessel function J v ( x) = ⎜ ⎟ M (v + 1/ 2, 2v + 1; 2ix)
v! ⎝ 2 ⎠
– The modified Bessel functions of the first kind
v
e ⎛ x ⎞
−x
I v ( x) = ⎜ ⎟ M (v + 1/ 2, 2v + 1; 2 x)
v! ⎝ 2 ⎠
Hermite Functions
• The Hermite functions are given by
(2n)! n 2(2n + 1)!
H 2 n ( x) = (−1)
n
xM (− n,1/ 2; x ), H 2 n +1 ( x) = (−1)
2
xM (− n,3 / 2; x 2 )
n! n!
• Comparing the Laguerre differential equation with the
confluent hypergeometric equation, we have
Ln ( x) = M (− n,1; x)
– The constant is fixed as unity, since
Ln (0) = 1
• The associated Laguerre functions
dm (n + m)!
m
x) = (−1) verification
L– (Alternate
n
m
L ( x) = is obtain
m n+ m
M (−by + 1; x)
n, mcomparing with
dx n!m!
the power series solution
Use of Hypergeometric Funtions
• Expressing special functions in terms of
hypergeometric and confluent hypergeometric
functions let the behavior of the special functions
follows as a series of special cases
• This may be useful in determining asymptotic
behavior or evaluating normalization integrals
• The relations between the special functions are
clarified